Letter (copy) : Aid for Spain
042-0048-001 Finance. JB/767 11th August, 1938. The Secretary, Spanish Medical Aid Committee. 24, New Oxford Street, London, W.C. Dear Sir, AID FOR SPAIN. I am enclosing herewith letter which we have to-day received from Mrs. C.M. Maloney of Chelmsford, Essex, together with postal order for 10s.6d. This contribution to your funds has evidently been sent to this office in error, and I shall be glad if you will acknowledge the receipt of this donation in due course. Yours sincerely, Accountant. 292/946/42/48